Integer programming on domains containing inseparable ordered pairs. Issue 4 (December 2018) - Busetto, Francesca; Codognato, Giulio; Tonin, Simone
Abstract: Using the integer programming approach introduced by Sethuraman et al. (2003), we extend the analysis of the preference domains containing an inseparable ordered pair, initiated by Kalai and Ritz (1978). We show that these domains admit not only Arrovian social welfare functions "without ties, " but also Arrovian social welfare functions "with ties, " since they satisfy the strictly decomposability condition introduced by Busetto et al. (2015). Moreover, we go further in the comparison between Kalai and Ritz (1978)'s inseparability and Arrow (1963)'s single-peak restrictions, showing that the former condition is more "respectable, " in the sense of Muller and Satterthwaite (1985).